Analysis Of Leadership Style And Work Motivation On Employee Performance In ‘Badan Kepegawaian’ Special Region Of Yogyakarta - Indah Ayu Prameswari; Muhammad Bakr Muhlison (Cita konsultindo, 2024)
This research, conducted during an internship program at Badan Kepegawaian Daerah DIY from February 1 to May 31, 2023, aimed to analyze the influence of leadership style and motivation on employee performance. Using a descriptive qualitative approach, primary data were collected through observations and interviews, and secondary data from work documents such as organizational structure, SOPs, and certificates. The snowball sampling method was employed, interviewing respondents until the researcher gathered sufficient information on the influence of leadership styles at the agency. The findings indicate that the head of Badan Kepegawaian Daerah DIY adopts a democratic leadership style, fostering openness and harmonious communication. This style involves the leader as part of the group, sharing responsibility and encouraging member participation in all organizational activities. However, the high work ethic of leaders often results in employees working beyond regular hours.